Sex-specific nociceptor modulation of the apical periodontitis transcriptome - Lillis, Katherine V.; Grinceviciute, Ruta; Diogenes, Anibal (Frontiers in Molecular Biosciences, 2024)
Introduction: Apical periodontitis (AP) is a painful disease that develops quickly following dental infections and is primarily characterized by robust inflammation surrounding the tissues of the affected tooth, resulting in disruption of bone homeostasis and periradicular bone loss. Moreover, there are distinct clinical presentations, symptoms, and responses to AP treatment between male and female subjects, creating a desperate need to further understand the sex-specific mechanisms of AP. Methods: With the growing evidence that nociceptors modulate AP development, we utilized RNA sequencing in nociceptor-ablated (Nav1.8 cre+/−, diphtheria toxin Alox+/−) transgenic mice to study the nociceptor regulation of the periapical lesion transcriptome using a rodent model of AP in female mice over 14 days. Results: Overall, we found that female mice exhibit unique patterns of differentially expressed genes throughout AP infection compared to male mice and that the expression of these genes is regulated by nociceptors. Additionally, nociceptor ablation results in a more significant enrichment of biological processes related to immune responses earlier compared to cre-control (Nav1.8 cre+/−) females and greater expression of genes involved in inflammatory processes and osteolytic activity. Discussion: Therefore, while nociceptor ablation augments inflammatory and bone resorption responses in both males and females in a mouse model of AP, transcriptomic analyses demonstrate that the mechanisms through which nociceptors modulate AP are distinct between sexes. These studies will provide the foundation needed to study further mechanisms of sex differences in AP, an area with a desperate need for investigation to treat current AP patients. Understanding these mechanisms can ultimately inform treatment options to alleviate suffering for millions of patients suffering from AP.